Cervicogenic headache alleviation after cervical coblation nucleoplasty: A prospective cohort study. Issue 39 (September 2016) - He, Liangliang; Yue, Jianning; Yang, Liqiang; Wu, Baishan; Cao, Guoqing; Guo, Yuna; Lai, Guanghui; Tang, Yuanzhang; Ni, Jiaxiang
Abstract : Abstract: A degenerative cervical disc is a pain generator for headaches, and headaches can benefit from cervical prolapse surgery. However, as an alternative intervention for open cervical surgery, no study has reported whether headaches can benefit from cervical nucleoplasty. The objective of this study was to evaluate the efficacy of cervical coblation nucleoplasty in the treatment of cervicogenic headaches. In a prospective cohort study performed between December 2013 and August 2015, 20 patients with cervicogenic headaches undergoing cervical nucleoplasty for shoulder-arm pain were recruited into group C, and 20 patients with cervicogenic headaches undergoing lumbar nucleoplasty for low back pain, matched for age and sex, were recruited into group L. Cervicogenic pain was diagnosed according to the International Headache Society criteria. During the 24-month follow-up, pain visual analog scale (VAS) scores were collected as the primary outcomes, and significant pain relief rate, Neck Disability Index (NDI) headache scores, and Patients Satisfaction Index (PSI) scores were recorded as secondary outcomes to evaluate headache severity and physical function postoperatively. During the 24-month follow-up, a significant decrease in headache VAS scores was observed in group C but not in group L. NDI and PSI scores in group C were better than those in group L. In comparison with the final follow-up, no significant differences in the NDI and PSI scores were found in all observations after surgery. In comparison to group L, ≥50% pain relief was significantly better in group C. No serious complications were observed except for ≤20% of ecchymoma at the needle insertion site. This prospective study indicated that cervicogenic headaches may benefit from nucleoplasty.